Intramuscular Fat in the Medial Gastrocnemius Muscle of People Who Have Had a Stroke - D'Souza, Arkiev; Bolsterlee, Bart; Herbert, Robert D. (Frontiers in Bioengineering and Biotechnology, 2020)
Objective To compare intramuscular fat fraction in people who have ankle contractures following stroke with the intramuscular fat fraction in control participants. Design mDixon MRI images were used to quantify intramuscular fat fractions in the medial gastrocnemius muscles of people who had experienced a hemiparetic stroke (n=14, mean age 60±13 years) and control participants (n=18, mean age 66±12 years). Results Intramuscular fat fractions were similar in the paretic and non-paretic sides of stroke patients (mean on paretic side 14.5%, non-paretic side 12.8%, difference 1.6%, 95% confidence interval -0.7 to 4.1%). The intramuscular fat fraction on the paretic side was higher than in the control group (mean intramuscular fat fraction in control muscles 7.6%; difference 7.8%, 95% confidence interval 4.6 to 10.9%). The difference between intramuscular fat fractions in non-paretic and control legs increased with age. Body mass index correlated positively with intramuscular fat fraction in the paretic muscles (P = 0.02). There was no association between medial gastrocnemius intramuscular fat fraction and dorsiflexion range. Conclusion Muscles of stroke patients had elevated intramuscular fat fractions compared to muscles from control participants which were not explained by differences in body mass index. There is no clear relationship between intramuscular fat in the medial gastrocnemius muscle and dorsiflexion range of motion.